Broad Ligament Fibroid: A Diagnostic Dilemma (BIRDEM Medical Journal, 2016)
Leiomyomas are the commonest of all pelvic tumors. One-fifth women of reproductive age group suffer from this condition. Tumors of broad ligament are rare. Most common solid tumor of the broad ligament is a leiomyoma. It can originate from the uterus or broad ligament itself. Here, we report a case of broad ligament leiomyoma in a woman having secondary infertility and it posed a diagnostic dilemma.Birdem Med J 2015; 5(2): 116-118